2010
DOI: 10.4012/dmj.2009-068
|View full text |Cite
|
Sign up to set email alerts
|

Effects of metal primers on bonding of adhesive resin cement to noble alloys for porcelain fusing

Abstract: This study evaluated the effects of metal primers on the bonding of adhesive resin to four pure metals (Au, Pd, Ag, Cu) and two noble alloys for porcelain fusing (high-gold and high-palladium content alloys). Bonding surface was polished with 600-grit silicon carbide paper and primed with one of the three metal primers (V-Primer, Metaltite, and M.L. Primer). Bonded specimens were fabricated by applying adhesive resin (Super-Bond C&B) on the primed surface. Shear bond strength (SBS) was determined both before a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 24 publications
(30 reference statements)
0
29
2
Order By: Relevance
“…Among these, acidic monomers are used for bonding tooth structure (1,2), whereas thiol or thione monomers are used for priming noble metal alloys (3)(4)(5). An adhesive resin initiated with tri-n-butylborane (TBB) derivative, in combination with thiol or thione primer, has been used for bonding between tooth structure and noble metal alloy (6,7), between indirect composite material and noble metal alloy (4,(8)(9)(10), and for metal-to-metal bonding (11)(12)(13)(14). In addition, TBB resin has been used in direct restoration (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…Among these, acidic monomers are used for bonding tooth structure (1,2), whereas thiol or thione monomers are used for priming noble metal alloys (3)(4)(5). An adhesive resin initiated with tri-n-butylborane (TBB) derivative, in combination with thiol or thione primer, has been used for bonding between tooth structure and noble metal alloy (6,7), between indirect composite material and noble metal alloy (4,(8)(9)(10), and for metal-to-metal bonding (11)(12)(13)(14). In addition, TBB resin has been used in direct restoration (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the highest SBS values achieved for pure Au and high-gold-content alloy were 33.5 MPa and 33.3 MPa with M.L. Primer 27) . Despite the differences in bond testing methodology, Si-AA-SS-2 exhibited comparable bonding ability in this study for Au (30.3 MPa) when pitted against the published bonding data (namely, 33.5 MPa 27) and 25.2 MPa 7) ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the availability of sulfur-containing monomers such as VBATDT and MTU-6 (6-methacryloyloxyhexyl-2thiouracil-5-carboxylate) that promote adhesion to precious alloys [35][36][37][38] could have improved the bond strength and bonding durability of cements.…”
Section: Discussionmentioning
confidence: 99%